2016
DOI: 10.18632/oncotarget.12731
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib-resistance is associated with increased levels of proteasome subunits and apoptosis-avoidance

Abstract: Bortezomib (BTZ), a proteasome inhibitor, is the first proteasome inhibitor to be used in clinical practice. Here we investigated the mechanisms underlying acquired bortezomib resistance in hepatocellular carcinoma (HCC) cells. Using stepwise selection, we established two acquired bortezomib-resistant HCC cell lines, a bortezomib-resistant HepG2 cell line (HepG2/BTZ) and bortezomib-resistant HuH7 cell line (HuH7/BTZ). The 50% inhibitory concentration values of HepG2/BTZ and HuH7/BTZ were respectively 15- and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 50 publications
2
27
0
Order By: Relevance
“…Proteasome inhibitors represent a new class of promising therapeutic drugs in cancer 2 , 3 . However, although several preclinical studies have shown that proteasome inhibition by bortezomib could represent a viable therapeutic strategy for treatment of HCC 10 12 , clinical results obtained in patients with unresectable HCC have been disappointing 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteasome inhibitors represent a new class of promising therapeutic drugs in cancer 2 , 3 . However, although several preclinical studies have shown that proteasome inhibition by bortezomib could represent a viable therapeutic strategy for treatment of HCC 10 12 , clinical results obtained in patients with unresectable HCC have been disappointing 13 .…”
Section: Discussionmentioning
confidence: 99%
“…At the molecular level, bortezomib treatment induces cell death through endoplasmic reticulum (ER) stress induction 4 7 , nuclear factor kappa B inhibition 8 , and caspase-8 activation 9 . However, although preclinical results have shown that bortezomib has antitumor effects in HCC 10 12 , a multicenter single-arm phase II trial conducted in cases of unresectable HCC showed that although bortezomib is well tolerated, it lacks significant activity 13 . Moreover, in many cases patients treated with bortezomib rapidly develop drug resistance, the mechanisms of which are poorly understood 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite initial clinical success in treating MM, many patients eventually relapsed from bortezomib therapy due to resistance development 27,28 . Bortezomib resistance is caused due to mutations in the binding pocket of PSMB5 subunit of proteasome that resulted in impaired drug binding.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of the direct mechanisms of Btz resistance were derived analyzed various tumor cell lines, including MM [ 10 , 11 ], lymphoma [ 26 ], leukemia [ 9 , 27 ], lung cancer [ 12 ], and hepatocellular carcinoma [ 14 ], with Btz. These studies suggested that Btz resistance is controlled by multiple factors, including alterations in PSMB5 expression or sequence, adjustment of biosynthesis of new proteins to reduce the ER stress [ 27 ], and upregulation of multiple proteasome subunits, such as β2 and β5 subunits, which enables cells to adapt to the selective proteasome inhibition resulting from Btz treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of CT-L activity is considered a key strategy for treating MM cells. However, several studies have proposed that the mechanism of action of Btz resistance is mainly associated with activity of the β5 subunit, such as mutations in PSMB5 (β5 subunit coding gene) [ 9 , 10 ] or upregulated expression of proteasome subunits [ 11 14 ]. Specifically, inhibiting the activity of the β5 subunit would not provide a sufficient anti-tumor effect in MM cases showing Btz resistance.…”
Section: Introductionmentioning
confidence: 99%